Tribological, thermal, dynamic and mechanical characteristics of low density polyethylene composites with iron scale - Bayraktar, Gamze; Demirel, Bilal; Yaras, Ali; Akkurt, Fatih; Ozkan, Dervis; Er, Yusuf (Elsevier, 2022)
The evaluation of wastes in various processes is an alternative to the production of innovative materials as well as eco-friendly. In the current paper, an industrial waste with high iron content (iron scale, F2O3) was incorporated into LDPE at different contents (5-20% by weight) and particle sizes (30-200 mu m). The raise of iron scale content and particle size under 10 N and 15 N loads caused an increase in the volume loss of the composites. The highest and lowest specific wear rates for all contents and particle sizes of iron scale under 10 N and 15 N loads were observed at 30 mu m and 120 mu m, respectively. The wear phenomenon occurred in the form of cracking and delamination mechanisms. As the particle size increased from 30 mu m to 200 mu m, the hardness value increased and the highest hardness (shore D = 49) was reached in the presence of 20% iron scale. The raise of iron scale content increased the elongation at break and did not significantly affect the tensile strength. The increase of particle size caused an increase in tensile strength, while a decrease in elongation at break was observed. The incorporation of iron scale did not significantly change the initial degradation temperature of LDPE and composites. Although there are partial differences at lower temperatures in terms of elastic and loss modulus of the samples, the general trend is a decreasing trend with the raise temperature. Overall, LDPE composites outperformed the pure LDPE in terms of mechanical and wear properties.
Keywords: Low -density polyethylene composites; Iron scale; Dynamic mechanical analysis; Tribological properties